STUDENT PERSPECTIVES ON CHEMISTRY LEARNING AND TEACHING IN A STEM FOUNDATION COURSE - Abidin, Nurul Nadia Zainal (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This study aimed to investigate the attitudes, challenges, and learning preferences of foundation-level STEM students in a Malaysian university chemistry course. A mixed-methods survey was conducted to identify key learning difficulties and perceptions of effective teaching strategies. The findings reveal a motivated but anxious student body, whose primary challenges involve the application of knowledge in calculations rather than understanding fundamental concepts. Although students rely on memorization, they express a strong desire for more active and visual learning methods, such as practice exercises and online videos. While satisfaction with the lecturer’s clarity and support was very high, qualitative feedback highlighted a clear need for more practice opportunities and supportive resources. The study concludes that a significant disconnect exists between students’ passive study habits and their desire for active, application-based learning, which likely fuels their anxiety. It is therefore recommended that educators foster a more active, visual, and supportive learning environment by integrating more problem-solving, utilizing multimedia, and providing differentiated support to better empower students and build their confidence.